Work overload is related to increased risk of error during chemotherapy preparation. (September 2019) - Carrez, Laurent; Bouchoud, Lucie; Fleury, Sandrine; Combescure, Christophe; Falaschi, Ludivine; Sadeghipour, Farshid; Bonnabry, Pascal
Purpose: Chemotherapy preparation units face peaks in activity leading to high workloads and increased stress. The present study evaluated the impact of work overloads on the safety and accuracy of manual preparations. Method: Simulating overwork, operators were asked to produce increasing numbers of syringes (8, 16, and 24), with markers (phenylephrine or lidocaine), within 1 h, in an isolator, under aseptic conditions. Results were analyzed using qualitative and quantitative criteria. Concentration deviations of < 5%, 5%–10%, 10%–30%, and >30% from the expected concentration were considered as accurate, weakly accurate, inaccurate, and wrong concentrations, respectively. Results: Twenty-one pharmacy technicians and pharmacists carried out 63 preparation sessions (n = 1007 syringes). A statistically significant decrease in the manufacturing time for one syringe was observed when workload increased (p < 0.0001). Thirty-nine preparation errors were recorded: 30 wrong concentrations (deviation > 30%), 6 mislabeling, 2 wrong diluents, and 1 wrong drug. There was no statistically significant difference in the mean concentration accuracy of final preparations across the three workloads. The overall error rate increased with the number of preparations made in 1 h: 1.8% for 8 preparations, 2.7% for 16 preparations, and 5.4% for 24 preparations (p < 0.05). Conclusion: Although pharmacy technicians and pharmacists were able to increase production speeds with no effect on mean concentration accuracy under stressful conditions, there were greater probability errors being made. These results should encourage actions to spread workloads out over the day to avoid peaks in activity.